2017
DOI: 10.1177/0963689717714102
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) presents in various forms ranging from mild alterations of consciousness to an unrelenting comatose state and death. In the most severe form of TBI, the entirety of the brain is affected by a diffuse type of injury and swelling. Treatment modalities vary extensively based on the severity of the injury and range from daily cognitive therapy sessions to radical surgery such as bilateral decompressive craniectomies. Guidelines have been set forth regarding the optimal management of TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
208
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(221 citation statements)
references
References 136 publications
0
208
0
13
Order By: Relevance
“…The importance of PACAP in the neuronal regeneration lies in the upregulation of endogenous PACAP and its receptors and the protective effect of exogenous PACAP after different central nervous system injury. The animal models not only can help us understand the pathophysiology of TBI, but allow us to develop interventions for preventing secondary injury, enhancing brain repair and improving recovery after TBI [74]. The results of the aforementioned animal experiments indicate that PACAP may also be a promising therapeutic agent in case of TBI due to its anti-inflammatory, anti-apoptotic and anti-oxidant effects (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of PACAP in the neuronal regeneration lies in the upregulation of endogenous PACAP and its receptors and the protective effect of exogenous PACAP after different central nervous system injury. The animal models not only can help us understand the pathophysiology of TBI, but allow us to develop interventions for preventing secondary injury, enhancing brain repair and improving recovery after TBI [74]. The results of the aforementioned animal experiments indicate that PACAP may also be a promising therapeutic agent in case of TBI due to its anti-inflammatory, anti-apoptotic and anti-oxidant effects (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress accompanies neurodegenerative disorders, causing neuronal dysfunctions and vascular damage [30,44]. The latest studies have shown that the level of oxidative stress is elevated in disorders of consciousness [7].…”
Section: Discussionmentioning
confidence: 99%
“…The latest study documented that MSC transplantation suppressed oxidative stress in Alzheimer's disease [26]. Studies on cell cultures and animal models show that MSC transplantation improved motor and receptive functions after cerebral stroke [27][28][29], TBI, spinal cord injury [30,31], and promoted nerve remodeling [32]. In rodents, injection of MSC after TBI leads to neuroprotection by maintaining blood-brain barrier integrity, promoting activated microglial apoptosis, and improving cognitive function [33][34][35].…”
mentioning
confidence: 99%
“…Despite intense and sustained efforts deployed for the development of new therapeutic strategies, very few clinical treatment options have been successful [32]. NFκB-mediated neuroinflammation is the driving force behind the secondary wave of degeneration.…”
Section: Discussionmentioning
confidence: 99%